Distributed Web browsing: supporting frequent uses and opportunistic requirements - Firmenich, Sergio Damian (2017)
Nowadays, the development of Web applications supporting distributed user interfaces (DUI) is straightforward. However, it is still hard to find Web sites supporting this kind of user interaction. Although studies on this field have demonstrated that DUI would improve the user experience, users are not massively empowered to manage these kinds of interactions. In this setting, we propose to move the responsibility of distributing both the UI and user interaction, from the application (a Web application) to the client (the Web browser), giving also rise to inter-application interaction distribution. This paper presents a platform for client-side DUI, built on the foundations of Web augmentation and End User Development. The idea is to empower end users to apply an augmentation layer over existing Web applications, considering both frequent use and opportunistic DUI requirements. In this work, we present the architecture and a prototype tool supporting this approach and illustrate the incorporation of some DUI features through case studies.